PREVENTION OF TUBERCULOSIS AT SCHOOL AGE-AWARENESS OF SECONDARY SCHOOL STUDENTS - Gabriela Tsankova; Bisera Yustiniyanova; Lyusi Kapreljan (Peytchinski Publishing, 2011)
Aim: carrying out of secondary school students' health awareness about tuberculosis' characteristics and its prophylaxis.Materials and methods: An anonymous inquiry examination of 190 students at the age of 15-18, 69 (36%) of who - boys and 121 (64%) girls in IX, X, XI classes, from 3 secondary schools in Varna. The inquiry consists of 32 questions, classified in 4 sections. SPSS ver. 19.0 software package was used for statistical data processing.Results: Studies show that the interviewed students are aware of the basic characteristics of tuberculosis. The research displays significant differences between girls and boys` answers. Boys are better grounded in the causes, the processes of transmission and the basic prophylactic measures for prevention of tuberculosis whereas girls are very knowledgeable about the main symptoms of the disease.